The turn of midnight - Walters, Minette (Mira, 2019)
As the year 1349 approaches, the Black Death continues its devastating course across England. In Dorseteshire, the quarantined people of Develish question whether they are the only survivors. Guided by their beloved young mistress, Lady Anne, they wait, knowing that when their dwindling stores are finally gone they will have no choice but to leave. But where will they find safety in the desolate wasteland outside? One man has the courage to find out. Thaddeus Thurkell, a freethinking, educated serf, strikes out in search of supplies and news. A compelling leader, he and his companions quickly throw off the shackles of serfdom and set their minds to ensuring Develish<U+2019>s future<U+2014>and freedom for its people. But what use is freedom that cannot be gained lawfully? When Lady Anne and Thaddeus conceive an audacious plan to secure her people<U+2019>s independence, neither foresees the life-threatening struggle over power, money and religion that follows<U+2026>